Suramin could block the activity of Arabinono-1, 4-lactone oxidase enzyme from Leishmania donovani: structure-based screening and molecular dynamics analyses. (31st October 2019) - Adinehbeigi, Keivan; Shaddel, Minoo; Khalili, Saeed; Zakeri, Alireza
Abstract: Background: Leishmania donovani, a parasitic protozoan causing visceral leishmaniasis, can lead to a dangerous and often fatal disease in humans. Current treatment for leishmaniasis may have severe side effects, low efficacy and high cost, hence an immediate need for new efficient drugs is essential. Arabinono-1, 4-lactone oxidase enzyme from Leishmania donovani (LdALO), which catalyzes the last step of the ascorbate biosynthesis pathway, has been considered as a potential target for antileishmanial drugs design. Methods: The current study was performed with an in silico approach to predict novel inhibitory molecules against the LdALO enzyme. Various modeling and refinement processes were employed to obtain a reliable 3D structure. Results: The best LdALO model with the highest qualitative model energy analysis score was predicted by the Robetta server and subsequently refined by 3D refine and ModLoop servers. The high quality of the final LdALO model was confirmed using model assessment software. Based on docking analysis results, we predicted 10 inhibitory molecules of a US Food and Drug Administration-approved library, with appropriate criteria regarding energy binding and interaction with the main functionally active sites of LdALO, indicating that they could be significant targets for further drug design investigations against L. donovani . Conclusion: Suramin is used to treat the first stage of African sleeping sickness and its mechanism of action is unknown. Our results showed that suramin was the best-predicted inhibitor compound for LdALO enzyme activity.